The Untouchables - De Palma, Brian, 1940-; Andy, Garcia; Charles Martin Smith; Richard Bradford; Robert De Niro; Sean Connery; Kevin Costner (USA Paramount Pictures, 1987)
Federal agent Elliot Ness assembles a personal team of mob fighters to bring Chicago crime boss Al Capone to justice using unconventional means during the mob wars of the 1920s. This fictionalized account of the arrest of Al Capone is heavy on style and gunfire. The end shootout combines a baby carriage and stairs with a nod to Eisenstein's _The Battleship Potemkin.
Federal Agent Elliot Ness sets out to take out Al Capone; because of rampant corruption, he assembles a small, hand-picked team.
David Mamet
Languages : English, German Subtitles : English, Turkish, Arabic
Keywords: Drama; History; Thriller; Crime